2022
DOI: 10.1002/app.52900
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of silk fibroin composite bone scaffold with polydopamine coating to enhance mineralization ability and biological activity for bone tissue engineering

Abstract: Bone tissue engineering plays an important role in the treatment of bone defects. Finding suitable bone graft substitute scaffolds is still a major challenge. In this study, we combined silk fibroin‐octacalcium phosphate composite with silk fibroin by freeze‐drying technology, and the freeze‐dried scaffolds were further surface‐modified with self‐polymerization by using dopamine. The silk fibroin/octacalcium phosphate/polydopamine composite bone scaffold was successfully constructed. The composition and struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The absorption peak at 3000–3500 cm –1 corresponded to the stretching vibration of primary amine −NH 2 , which became stronger after PDA deposition in Figure a due to the more amino groups in PDA. This may also indicate hydrogen bonding at the interface of PDA and silks in PDA-modified silks . In Figure b, when the fiber was only coated with ESO, a distinct absorption peak at 1745 cm –1 appeared, which was attributed to the ester groups of ESO .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The absorption peak at 3000–3500 cm –1 corresponded to the stretching vibration of primary amine −NH 2 , which became stronger after PDA deposition in Figure a due to the more amino groups in PDA. This may also indicate hydrogen bonding at the interface of PDA and silks in PDA-modified silks . In Figure b, when the fiber was only coated with ESO, a distinct absorption peak at 1745 cm –1 appeared, which was attributed to the ester groups of ESO .…”
Section: Resultsmentioning
confidence: 91%
“…This may also indicate hydrogen bonding at the interface of PDA and silks in PDAmodified silks. 42 In Figure 3b, when the fiber was only coated with ESO, a distinct absorption peak at 1745 cm −1 appeared, which was attributed to the ester groups of ESO. 43 After ESO was later introduced, the spectrum of Ap−PDA−ESO also displayed the absorption peak of ester groups, indicating that ESO was grafted successfully.…”
Section: Structure and Compositionmentioning
confidence: 95%
“…Therefore, the development of bionic bone tissue engineering scaffolds is of particular importance and can achieve a very good effect if relevant natural materials are combined with the development of bone scaffolds [ 161 , 162 ]. For example, Peng et al used SF, polydopamine (PDA), and octacalcium phosphate (OCP) as materials to prepare a SF/OCP/PDA three-dimensional network bio-scaffold using a freeze-drying method, which showed more positive compressive capacity and better biocompatibility, and the scaffold could effectively accelerate the phospholime deposition rate, which can be used as a potential material for bone defect repair ( Figure 9 B) [ 159 ]. Kolanthai et al first prepared a SA–chitosan–Col scaffold using a freeze-drying method, and after modification by graphene oxide (GO), an SA–chitosan–Col-GO biocomposite scaffold was made, which possessed stable mechanical properties and good biocompatibility, and the growth and proliferation effects of the mouse osteoblasts were promoted on this scaffold, which could be used to promote bone tissue regeneration ( Figure 9 C) [ 160 ].…”
Section: Applicationmentioning
confidence: 99%
“…( A ) Schematic diagram of the modification of ALMA using alginate [ 158 ]. ( B ) Schematic diagram of the preparation of SF/OCP/PDA scaffold [ 159 ]. ( C ) Schematic diagram of the preparation of SA–Chitosan–Col–GO composite scaffold [ 160 ].…”
Section: Figurementioning
confidence: 99%
“…The following supporting information can be downloaded at : Table S1: A synopsis of each study described within this article, including the authors and publication year, material and tissue type, and testing and mechanical property information, as well as a brief summary, where appropriate, of each research paper reported thus far [ 29 , 64 , 113 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 152 , 156 , 157 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 170 , 190 ].…”
mentioning
confidence: 99%